2013
DOI: 10.1073/pnas.1315622110
|View full text |Cite
|
Sign up to set email alerts
|

Silencing synuclein at the synapse with PLK2

Abstract: The significance of α-synuclein (α-syn) phosphorylation to Parkinson disease (PD) pathology has been controversial since the initial identification of this posttranslational modification in intracellular Lewy bodies (1, 2). The modification of serine-129 (S129), which appears to be the most common phosphorylation site on α-syn (3, 4), has had the focus of attention. Although several different kinase families have been linked to modification of S129 in vitro, definitive in vivo evidence that a given kinase fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Notably, controversial publications have generated considerable debate, suggesting that PLK2 may have a putative toxic or protective attribute, which is probably due to the complex interplay of factors that occur in dopamine neurons. In this sense, Oueslati et al (2013) demonstrated that PLK2 enhances α-syn clearance and suppresses its toxicity in vivo while Looyenga and Brundin (2013) suggested that prolonged periods of PLK2 activity may be detrimental to neurons. There is thus a lack of consensus concerning whether α-syn phosphorylation could lead to neuronal toxicity and LB aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, controversial publications have generated considerable debate, suggesting that PLK2 may have a putative toxic or protective attribute, which is probably due to the complex interplay of factors that occur in dopamine neurons. In this sense, Oueslati et al (2013) demonstrated that PLK2 enhances α-syn clearance and suppresses its toxicity in vivo while Looyenga and Brundin (2013) suggested that prolonged periods of PLK2 activity may be detrimental to neurons. There is thus a lack of consensus concerning whether α-syn phosphorylation could lead to neuronal toxicity and LB aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…The synaptic protein SPAR is a PLK2 substrate involved in the regulation of neuronal plasticity [11]. In addition, PLK2 can phosphorylate and promote selective autophagic clearance of α-synuclein, a synaptic protein that accumulates in the Lewy bodies of Parkinson’s disease, a neurodegenerative condition associated with mitochondrial dysfunction and oxidative stress [1216]. These different functions of PLK2 in proliferating and post-mitotic cells suggest that the phosphorylation of different substrates represents cell type-specific adaptive processes activated under conditions of stress and is also consistent with the initial identification of PLK2 as an immediate early response gene [17].…”
Section: Introductionmentioning
confidence: 99%
“…α-Synuclein is constitutively phosphorylated at low levels in normal brain and an accumulation of α-synuclein pS129 in Lewy bodies is observed in Parkinson disease and other synucleinopathies. Although the pathophysiology of the Ser-129 phosphorylation in Parkinson's disease is not completely understood and it has not been clarified whether this phosphorylation is protective or harmful for neurons, PLK2 is considered a very promising target for Parkinson disease treatment [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%